Zero Energy Cooling Technology for Storage of Cavendish Banana Fruits - Rahaman, Adams Abdul; Alhassan, Nasiru; Andrews, Agyemang Dua (Journal of Postharvest Technology, 2015)
Postharvest storage solutions are required to increase sales of horticultural produce and provide producers with options to address the crisis of low market prices during the harvest season. However, opportunities to develop and adopt appropriate strategies by farmers in developing countries are limited. There has been a concern for the need for alternative sources of energy to the stress with global energy supplies to industries and domestic uses. This project involved the construction of Zero Energy Cold Chamber (ZECC) for the cooling and storage of Fresh Banana fruits. This investigation was undertaken to find out the effects of using Zero Energy Cold Chamber and House Hold Fridge (HHF) on weight loss, colour changes and consumer acceptance of fresh Cavendish Banana fruit. A total of 105 fruits were used for the experiment. The Banana was divided into three to represent the treated and untreated samples. The respective weights of the fruits were recorded after air drying, stored and monitored for an experimental period of eight (8) days. Thirty five fruits in bunches of five was stored in the ZECC, thirty five fruits were also stored in HHF and thirty five was left at room temperature as control. Completely Randomized Design (CRD) was the experimental design used. The analysis of the data was done using a MiniTab version 16. The single factor analysis of variance was used at 5% alpha level. The Cavendish Banana fruits stored in the HHF maintained an average colour of 2.0 throughout the entire experimental period, and the fruits stored in the ZECC produced an average colour of 5.0 when the experiment was terminated on day 8 compared with the CTS with 7.0 as the final stage of Banana ripeness. Average weight loss percentage was greater (5.91%) in Bananas, which were stored at ZECC than those, which were stored at HHF with average weight loss (4.90%) on the 8 day. Panelists preferred Bananas which were stored in ZECC to Banana stored in HHF. Significant differences were observed on the decay severity of the fruits stored in the different structures. Considering the performance of the ZECC on the parameters assessed, it can safely be stated that the ZECC can be adopted by small scale operators for handling fresh fruits for a reasonable duration in cooling and storage.